2021
DOI: 10.1016/j.bios.2020.112703
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in biosensors for inflammatory biomarkers of SARS-CoV-2 during 2019–2020

Abstract: COVID-19 pandemic has affected everyone throughout the world and has resulted in the loss of lives of many souls. Due to the restless efforts of the researchers working hard day and night, some success has been gained for the detection of virus. As on date, the traditional polymerized chain reactions (PCR), lateral flow devices (LFID) and enzyme linked immunosorbent assays (ELISA) are being adapted for the detection of this deadly virus. However, a more exciting avenue is the detection of certain biomarkers as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 85 publications
(97 reference statements)
0
18
0
1
Order By: Relevance
“…Increasing amounts of evidence suggest that a system-wide inflammatory response and a cytokine storm type syndrome plays a crucial role in the progression of COVID-19 and it is therefore now established to be one of the disease hallmarks [ [41] , [42] , [43] ]. This was attributed to the recruitment of immune cells triggered by a rapid rate of viral replication leading to the release of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amounts of evidence suggest that a system-wide inflammatory response and a cytokine storm type syndrome plays a crucial role in the progression of COVID-19 and it is therefore now established to be one of the disease hallmarks [ [41] , [42] , [43] ]. This was attributed to the recruitment of immune cells triggered by a rapid rate of viral replication leading to the release of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yao and coworkers (2020) and Tersalvi and coworkers (2020), the disease severity is directly related to the D-dimer levels ( 12 , 13 ). Garg and coworkers (2021) postulated that elevated levels of inflammatory biomarkers such as procalcitonin (PCT), C-reactive protein (CRP), ferritin (FT), and Interleukin-6 (IL-6) are indicators of the severity of COVID-19 infections ( 14 ).…”
Section: Biological Materials and Indicators Of Covid-19 Diagnosismentioning
confidence: 99%
“…By monitoring these biomarkers, infections with low SARS-CoV-2 RNA are also predicted in patients where traditional tests miss. In this area, nanoparticles are also used to develop several COVID-19 diagnosis methods ( 14 ). Several types of nanoparticles used in SARS-CoV-2 detection methods are given in Figure 1 .…”
Section: Nanoparticle-based Detection Strategies Of Covid-19mentioning
confidence: 99%
“…To be specific, chest CT scans showed relatively low specificity and only diagnose patients at the later stage after infections. Immunoassays were developed for the detection of immunoglobulin G (IgG) and immunoglobulin M (IgM) in serum samples (Carter et al, 2020; Ou et al, 2020), which showed high sensitivity and selectivity based on antigen‐antibody interactions (Garg et al, 2021). Unfortunately, it took approximately 13 days after infection for the seroconversion of IgG and IgM at a detectable level, making early diagnosis nearly impossible.…”
Section: Introductionmentioning
confidence: 99%